Proposed knowledge transfer key factors model in Malaysian higher education institutions - Rosle Mohidin; Roselina Ahmad Saufi; Roslinah Mahmud (AMER and cE-Bs by e-International Publishing House, Ltd., UK, 2024)
Knowledge transfer involves transmitting not just information, but also experience and best practices, known as tacit knowledge, enriching understanding. Effective transfer requires human capital skills, knowledge types, methods, and organizational support. This study examines factors influencing knowledge transfer projects in Malaysian higher education. Identified influencers include Higher Education Institutions Capacity, Academia Capability, Graduate Interns Capability, KT Partner Organization, Relational Elements, Technology Augmentation, External Factors, and Knowledge Transfer Mechanism. The study suggests Knowledge Transfer Mechanism and government policies mediate this model.